Correction of SPT (Standard Penetration Test) between Comparison of Energy Measurement in the Field and Seed Method (1985) - Muhammad Farhan Syahputra; Togani Cahyadi U (Universitas Negeri Semarang, 2024)
The use of the Standard Penetration Test (SPT) method has a very important role in the field of geotechnical engineering, especially in obtaining information related to soil characteristics under the surface. The data obtained from the SPT test is widely used in various applications, one of which is slope stability analysis, especially in areas with high potential for landslide disasters. This research was conducted as a form of the author's scientific contribution in highlighting the difference in energy produced by the SPT tool in the field compared to the results of the theoretical calculation approach. The research methodology includes the collection of data from the results of tax return testing in the field, which is then analyzed using the calculation method of the Seed method (1985). In the energy measurement in the field, the energy ratio (ER) was obtained of 56.3-77.7%. The average energy measurement at the BH-1, BH-2, and BH-3 test points was obtained at 70.9% each; 70.4%; and 64.8%. The results of the correction comparison showed the difference between the energy return from the energy measurement test in the field and the theoretical calculation. At depths of 0-10m it is 7-32% and at depths of 10-20m it is 7-15%. Corrections using the Seed method (1985) showed a relatively higher error rate compared to the results of direct energy measurements in the field. Taking this into account, the use of energy data obtained directly is considered more representative of actual conditions in the field and more reliable in the correction value of tax returns.